GE_GERICHTE P/20784/2024 vom 27. Januar 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE LE PATRIMOINE;BAILLEUR(BAIL À LOYER);CHOSE LOUEE;LOCAL PROFESSIONNEL | CPP.310.al1.leta; CP.137; CP.138